Burden of tobacco-related cancers in urban, semi-urban and rural setting of Nepal: Findings from population-based cancer registries 2019. - Uma Kafle Dahal; Meghnath Dhimal; Atul Budukh; Kopila Khadka; Sudha Poudel; Gehanath Baral; Pradip Gyanwali; Anjani Kumar Jha; Sandhya Chapagain (PLoS ONE)
Background Nepal is one of the high prevalent countries for tobacco use in Southeast Asia regions. Tobacco related cancer share the major burden since a decade, however, population-based estimates is still lacking. This study provides results from population-based cancer registries on tobacco-related cancer (TRCs) burden in Nepal. Methods The data were collected by population-based cancer registry conducted in nine districts by Nepal Health Research Council. The districts were categorized in urban, semi-urban and rural regions on the basis of geographical locations and facilities available in the regions. Analysis was done to identify tobacco-associated cancer incidence, mortality and patterns along with cumulative risk of having cancer before the age of 75 years. Results Tobacco-related cancer was 35.3% in men and 17.3% in women. We found that every one in 36 men and one in 65 women developed tobacco-related cancer before age 75 in Nepal. Cancer of lung, mouth, esophagus and larynx were among the five most common tobacco-related cancers in both men and women. The incidence of tobacco-associated cancers was higher in urban region with age adjusted rate 33.6 and 17.0 per 100,000 population for men and women respectively compared to semi-urban and rural regions. Tobacco-associated cancer mortality was significantly higher compared to incidence. Conclusion The prevalence of tobacco-related cancer found high in Nepal despite of enforcement of tobacco control policy and strategies including WHO framework convention on tobacco control. Concerned authorities should focus towards monitoring of implemented tobacco control policy and strategies.